Japanese Exchange Students’ Academic and Social Struggles at an American University - Sato, Takahiro; Hodge, Samuel R. (Journal of International Students, 2015)
The purpose of this study was to identify and analyze the views of exchange students from Asia about their academic and social experiences at an American university. The participants were eight exchange students from Japan (four men and four women). This study was descriptive-qualitative (Patton, 2002). The data sources were a demographic survey and two semi-structured interviews conducted during the participants’ study abroad sojourn. The interview data were analyzed using the constant comparative method (Merriam, 1998). The emergent themes were (a) social distance contributes to academic struggles, (b) collectivism positioned against individualism, (c) isolation in group discussions, and (d) professors’ negativity. We include recommendations aimed at improving international students’ academic and social experiences at American universities.